Halal Certification for MSMEs: what Drives the Interest of MSMES in Indonesia and Malaysia? - Suryaningsih, Sri Abidah; Indrarini, Rachma; Nurafini, Fira; Munir, Maryam Bte Badrul; Binti Zakaria, Zalina; Nurillah, Shinta Lintang (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study explores the factors influencing interest in halal certification, focusing on certification fees, government involvement, and the certification process, particularly for halal MSMEs (Micro, Small, and Medium Enterprises). A survey of 65 respondents from businesses in Indonesia and Malaysia was analyzed using Smart PLS 3.0, a tool for Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that certification fees (p-value = 0.226) and government involvement (p-value = 0.966) do not significantly affect interest, while the certification process (p-value = 0.009) has a significant impact. These findings suggest that simplifying the certification procedure could increase participation, especially for MSMEs facing challenges related to cost and understanding the process. The study’s practical implication is that certification bodies should prioritize simplifying the process to encourage more MSMEs to pursue halal certification. This research provides valuable insights for academic research, industry practices, and MSME empowerment.